Oral human papillomavirus infection among smokeless tobacco-using tribal women in Mysuru, India - Kavitha Ravi; Tanvi Kaur; Anisa S Khan; Benjamin Pope; Kim Y Nguyen; Kiranmayee Muralidhar; Karl Krupp; Brenda Y Hernandez; Angela Sy; Purnima Madhivanan; Vivek R Nerurkar (Wolters Kluwer Medknow Publications, 2023)
Smokeless tobacco (SLT) is consumed by more than 300 million people worldwide. Studies show high use among Indian indigenous women who are also at high risk for oral cancers. Both human papillomavirus infection (HPV) and SLT have been associated with oral cancer, this study examined the presence of high-risk HPV in oral samples collected from tribal smokeless tobacco users in Mysuru, India. Between June and August 2019, 100 tribal females (50 SLT-users and 50 non-users) from rural Mysuru District, Karnataka, were enrolled in a cross-sectional study. Following informed consent, demographic data and oral samples were collected and processed using a digene HC2 High-Risk HPV DNA test (Qiagen, USA). On average participants were 45.5 (SD: ±6.6) years. Chronic SLT users were mostly married (73%), Hindu (100%), illiterate (62%), and employed (90%). One woman was positive for high-risk HPV infection. Oral HPV infection was low in this sample and this is consistent with the literature from other low and middle-income countries. SLT use is high in this group so interventions to reduce tobacco use are warranted.